2020
DOI: 10.11606/issn.1678-4456.bjvras.2020.171082
|View full text |Cite
|
Sign up to set email alerts
|

Body fat evaluation in Colombian Paso horses: body condition score and morphometric and ultrasound measurements

Abstract: The body condition score (BCS) is insufficient in determining the amount of body fat in horses, thus defining obesity. Measurement of the subcutaneous fat thickness (SFT) by ultrasonography should be considered as an appropriate method in the definition of fat distribution at different body locations in horses. Therefore, this study aimed to 1) characterize the SFT in three different anatomical locations (i.e. neck, lumbar region, and gluteal region); 2) evaluate the relationship between BCS and SFT; 3) determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Other more objective metrics for identifying obesity in horses include the percentage of body fat, which has a strong correlation with the amount of fat tissue (Westervelt et al, 1976). The average body fat in Crioulo horses was higher than in Thoroughbreds (Fonseca et al, 2013) and Colombian Paso Fino horses (Cabrera & Valencia, 2020), and similar to values described for Icelandic horses (Jansson 3 and 4), indicative of muscle content. Greater FFM suggests a larger muscle mass and, consequently, greater strength potential, while an increased percentage of body fat is known to negatively affect performance due to elevated energy requirements (Kearns et al, 2002).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Other more objective metrics for identifying obesity in horses include the percentage of body fat, which has a strong correlation with the amount of fat tissue (Westervelt et al, 1976). The average body fat in Crioulo horses was higher than in Thoroughbreds (Fonseca et al, 2013) and Colombian Paso Fino horses (Cabrera & Valencia, 2020), and similar to values described for Icelandic horses (Jansson 3 and 4), indicative of muscle content. Greater FFM suggests a larger muscle mass and, consequently, greater strength potential, while an increased percentage of body fat is known to negatively affect performance due to elevated energy requirements (Kearns et al, 2002).…”
Section: Resultsmentioning
confidence: 74%
“…In a study, Andalusian stallions exhibited higher subcutaneous adipose deposits and neck morphometrics related to sex dimorphism (Martin-Gimenez et al, 2018). Conversely, Jensen et al (2016) and Cabrera and Valencia (2020) found no sex influence on morphometric evaluations. In another study, despite higher NC:HW in a group with an obese body condition score, no correlation with neck fat deposit was found (Fitzgerald et al, 2019), differing from the present study in which this measurement was associated with fat depth on the neck in males and CNS in females.…”
Section: Resultsmentioning
confidence: 93%